The Greek Version of the Blended Teaching Readiness Instrument (BTRI): Results of the Pretest Study and the Content Validation - Giannoulas, Angelos; Kalamatianos, Antonios; Kounenou, Kalliopie (Online Learning, 2025)
During the Covid-19 pandemic education systems policy makers realized the importance of being able to communicate using technology and, at the same time, to maintain their pursuits. As a consequence, a different approach to education followed, blended learning. Literature review revealed a lack of psychometric tools related to blended teaching readiness in Greece. Consequently, the purpose of this study was the translation and the adaptation from English language to Greek of the “Blended Teaching Readiness Instrument” (BTRI). The research instrument assesses five instructional modules: teacher attitudes, learning activities, use of digital data, learning environments, and online interaction. The present study showed that the two versions of the instrument, the original and the targeted, are fully equitable in terms of conceptual and adaptation meaning, with concepts of the same meaning in Greek language. The research group considers that the final translated version corresponds to the original English version.